The significance of victim ideality in interactions between crime victims and police officers - Inzunza, Miguel (International journal of law, crime and justice, 2022)
A crime victim's first contact with the police may strongly influence subsequent investigations and prosecutions, as well as the crime's impact on the victim. The outcomes of such contacts may depend strongly on the degree to which the victim exhibits the characteristics of an ideal victim. This study sought to find valid ways of evaluating the constructs of victim ideality and police empathy, and to clarify the relationship between the two considering background factors, and outcomes. With a cross-sectional design data were collected from approximately 300 crime victims from cities in Colombia using a questionnaire. The data were analyzed using SEM, MIMIC, and logistic regression models. Being an ideal victim was found to influence the empathy displayed by police (as perceived by the victims), which in turn influenced factors important to citizens exposed to crime. Several areas in need of development based on the principles of procedural justice are identified.